Validation of the transplant conditioning intensity (TCI) index for allogeneic hematopoietic cell transplantation - Spyridonidis, Alexandros; Labopin, Myriam; Gedde-Dahl, Tobias; Ganser, Arnold; Stelljes, Matthias; Craddock, Charles; Wagner-Drouet, Eva Maria; Versluis, Jurjen; Schroeder, Thomas; Blau, Igor Wolfgang; Wulf, Gerald G.; Dreger, Peter; et al. (Bone marrow transplantation, 2024)
The intensity of the conditioning regimen given before allogeneic hematopoietic cell transplantation (allo-HCT) can vary substantially. To confirm the ability of the recently developed transplant conditioning intensity (TCI) score to stratify the preparative regimens of allo-HCT, we used an independent and contemporary patient cohort of 4060 transplant recipients with acute myeloid leukemia meeting inclusion criteria from the discovery study (allo-HCT in first complete remission, matched donor), but who were allografted in a more recent period (2018-2021) and were one decade older (55-75 years, median 63.4 years), we assigned them to a TCI category (low n = 1934, 48%; intermediate n = 1948, 48%, high n = 178, 4%) according to the calculated TCI score ([1-2], [2.5-3.5], [4-6], respectively), and examined the validity of the TCI category in predicting early non-relapse mortality (NRM), 2-year NRM and relapse (REL). In the unadjusted comparison, the TCI index provided a significant risk stratification for d100 and d180 NRM, NRM and REL risk. In the multivariate analysis adjusted for significant variables, there was an independent association of TCI with early NRM, NRM and REL. In summary, we confirm in contemporary treated patients that TCI reflects the conditioning regimen related morbidity and anti-leukemic efficacy satisfactorily and across other established prognostic factors.